Brian Cherney: Collaborator and Composer - Beckwith, John (Intersections, 2017)
This article includes comments on some of Cherney’s compositions, and an account of his work on Weinzweig: Essays on His Life and Music (Waterloo: Wilfrid Laurier University Press, 2011), of which he and John Beckwith were the co-editors. Cherney’s approach to composing equips him for dealing with a wide range of musical questions, and his exceptional command of both German and Jewish history (as evidenced, for example, in his University of Toronto dissertation on the Bekker-Pfitzner controversy of 1919, and in his essay on the sources of Weinzweig’s radicalism in the 2011 publication) has in turn suggested avenues of exploration in his creative work. Further observations touch on his gift for parody and musical in-jokes.